Propuesta De Intervención De Los Niveles Del Burnout En Los Auxiliares De Enfermería (2023)
Burnout syndrome is a phenomenon that affects the physical and mental well-being of healthcare workers (Leiter, 2022). A mixed descriptive research study was conducted to identify and analyze the levels of Burnout and its main areas of impact among nursing assistants at the Intermediate Health Unit of Ibagué (U.S.I-E.S.E). The Maslach Burnout Inventory (MBI) test was used to determine potential levels of burnout among nursing assistants in the emergency area. Additionally, a prevention program was designed to promote proper management of workrelated stress among healthcare personnel.